The knowledge of movement experts about stretching effects: Does the science reach practice? - Warneke, K.; Konrad, A.; Wilke, J. (PLOS ONE, 2024)
Objective Stretching is performed with numerous purposes in multiple settings such as prevention, rehabilitation, fitness training and sports. Its patterns of use substantially depend on the education and beliefs of health care and exercise professionals as they represent the multiplicators recommending and prescribing interventions to clients, patients and athletes. This study investigated movement experts` knowledge about the scientific evidence on stretching effects.